Pengambilan Keputusan Dalam Pemilihan Mesin Filler Syrup Dengan Metode AHP-TOPSIS Pada PT X - Danny Willyandi (Universitas Katolik Parahyangan, 2022)
PT X is a pharmaceutical company and one of its products is cough syrup. The company wants to install a new filler machine to support their business development. There are 4 machine brands will be chosen by the company which are ITM, 3CR, IMA, MCS. This research focuses on filler machine selection for the production line. Research objectives are to determine the priority criteria and the best alternative filler machine. Using AHP-TOPSIS method where AHP method is used for weighting the assessment criteria while TOPSIS method is to sort alternative machines. The company decides there are 5 assessment criteria which are machine price, filling accuracy, filling speed, lead time availability and maintenance team; where the highest weight on maintenance team with 0,34. Based on TOPSIS method, the best alternative machine comes from the IMA brand with preference value of 0,9084. Sensitivity analysis shows machine price and filling speed could affect the selected machine. This research conclusion is AHP-TOPSIS method can be used as a decision-making framework in machine selection and the IMA brand is decided to be installed on the production line.